Método das tríades na validação de um questionário de frequência alimentar para avaliar o consumo de sódio, potássio e magnésio de hipertensos e/ou diabéticos - Amorim, Michele Ferro de (2014)
Dietary surveys under different methods of approach are used to assess the dietary intake of the population, among them is the Food Frequency Questionnaire ( FFQ ) . This is one of the most commonly used in epidemiological studies to assess individual food intake of foods and nutrients over a long period of time , thus being the most appropriate method to assess the relationship between diet and chronic diseases methods .Valid information is important and essential in interpreting the results of studies using FFQ to clarify the association between diet and disease . However , measurement errors often underestimate the estimates obtained in epidemiological studies . Thus , the validity of the instrument , ie , the degree to which it measures what it purports to measure must be evaluated so that it is possible to obtain more reliable information . In the process of validation of a FFQ , other dietary surveys as recall 24hours ( Rec24h ) and food diaries are often used as the reference method . Moreover, the biomarkers analyzed for nutrients can also be used for validation. When information from the FFQ Rec24h (or food record ) and biomarkers are available , a method known as the method of triads , can be applied to validate the FFQ . This method allows comparison of food consumption , estimated by the three methods with the " true intake " . As this basis , this thesis was drawn from a study that aimed to evaluate the validity of estimated intake of sodium, potassium and magnesium of a FFQ developed for hypertension and / or diabetes , the city of Maceió- AL , by the method triads . Through this study , we observed that the reported FFQ is valid to assess magnesium intake , with a validity coefficient of 0.93 . Correlation coefficients below the recommended FFQ between biomarkers and for sodium and potassium , whereas , when comparing the average sodium intake FFQ obtained by considering the intake of sodium coming from the added salt, the result was observed in intake approached obtained by biomarkers ( p = 0.95) . Based on these results , it is concluded that the reported FFQ is necessary for analysis of magnesium and probably not quantify the salt addition and a great variability in dietary intake may have passed to the correlation coefficients between the FFQ and biomarkers for sodium and potassium respectively. Thus, the QFA may be useful for evaluating these minerals , but with the quantification of the addition salt is accompanied by biochemical marker 24h urinary excretion , to improve the estimated intake .